2018
DOI: 10.15252/embj.201798728
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hed1 and Rad54 binding during maturation of the meiosis‐specific presynaptic complex

Abstract: Most eukaryotes have two Rad51/RecA family recombinases, Rad51, which promotes recombination during mitotic double-strand break (DSB) repair, and the meiosis-specific recombinase Dmc1. During meiosis, the strand exchange activity of Rad51 is downregulated through interactions with the meiosis-specific protein Hed1, which helps ensure that strand exchange is driven by Dmc1 instead of Rad51. Hed1 acts by preventing Rad51 from interacting with Rad54, a cofactor required for promoting strand exchange during homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 83 publications
(254 reference statements)
6
74
1
Order By: Relevance
“…Genetic and biochemical data have demonstrated that Hed1 interacts specifically with Rad51 (15,39), and Hed1-GFP complements a hed1D strain, indicating that the fluorescent protein retains function (14). Consistent with these findings, we can readily detect Hed1-GFP binding to Rad51, but we are unable to detect any GFP-Hed1 association with Dmc1 ( Figure 2A) (40). Therefore, we consider Hed1-GFP to be good proxy for defining the location of Rad51 within the presynaptic complex.…”
Section: Models For Mixed Recombinase Filaments -Rad51supporting
confidence: 77%
See 2 more Smart Citations
“…Genetic and biochemical data have demonstrated that Hed1 interacts specifically with Rad51 (15,39), and Hed1-GFP complements a hed1D strain, indicating that the fluorescent protein retains function (14). Consistent with these findings, we can readily detect Hed1-GFP binding to Rad51, but we are unable to detect any GFP-Hed1 association with Dmc1 ( Figure 2A) (40). Therefore, we consider Hed1-GFP to be good proxy for defining the location of Rad51 within the presynaptic complex.…”
Section: Models For Mixed Recombinase Filaments -Rad51supporting
confidence: 77%
“…To test this prediction, we sought to determine whether any Rad51 remained bound to the mixed recombinase filaments after ATP depletion by using Hed1-GFP to detect Rad51. Importantly, our previous experiments have shown that Hed1-GFP does not bind to either RPA-ssDNA or Dmc1-ssDNA, and presence of bound Hed1 is strictly dependent upon the integrity of the Rad51-ssDNA (40). Therefore, Hed1-GFP would only be able to bind to the presynaptic complexes if Rad51 remained present after ATP depletion.…”
Section: Models For Mixed Recombinase Filaments -Rad51mentioning
confidence: 94%
See 1 more Smart Citation
“…The Rad51-Binding Factor Hed1 Does Not Affect Srs2. During meiosis, Rad51 strand-exchange activity is down-regulated by the meiosis-specific Rad51-binding factor Hed1, which prevents Rad54 from associating with Rad51-ssDNA filaments (51)(52)(53). Importantly, we used GFP-tagged Hed1 in DNA curtain assays to identify the locations of Rad51 within mixed recombinase filaments containing Rad51 and Dmc1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we used GFP-tagged Hed1 in DNA curtain assays to identify the locations of Rad51 within mixed recombinase filaments containing Rad51 and Dmc1 (Fig. 4B) (52). Bulk biochemical assayed revealed that Hed1-GFP has no appreciable impact on Srs2 ATP hydrolysis activity (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%